Giacomo Ceruti a compassionate eye - Gasparotto, Davide; Coccoli, Lorenzo (Getty Trust Publications, 2023)
The northern Italian artist Giacomo Ceruti (1698-1767) was born in Milan and active in Brescia and Bergamo. For his distinctive, large-scale paintings of low income tradespeople and individuals experiencing homelessness, whom he portrayed with dignity and sympathy, Ceruti came to be known as Il Pitocchetto (the little beggar). 00Accompanying the first US exhibition to focus solely on Ceruti, this publication explores relationships between art, patronage, and economic inequality in early modern Europe, considering why these paintings were commissioned and by whom, where such works were exhibited, and what they signified to contemporary audiences. Essays and a generous plate section contextualize and closely examine Ceruti?s pictures of laborers and the unhoused, whom he presented as protagonists with distinct stories rather than as generic types. Topics include depictions of marginalized subjects in the history of early modern European art, the career of the artist and his significance in the history of European painting, and the period discourses around poverty and social support. A detailed exhibition checklist, complete with provenance, exhibition history, and bibliography, provides information critical for the further understanding of Ceruti?s oeuvre.00Exhibition: J. Paul Getty Museum, Getty Center, Los Angeles, USA (18.07. - 29.10.2023).